A psychometric assessment of the Brief Situational Confidence Questionnaire for Marijuana (BSCQ-M) in juvenile justice-involved youth. (February 2022) - Micalizzi, Lauren; Sokolovsky, Alexander W.; Delaney, Daniel J.; Gunn, Rachel L.; Hernandez, Lynn; Kemp, Kathleen; Spirito, Anthony; Stein, L.A.R.
Highlights: This study provided the first test of the psychometric properties of the BSCQ-M. Findings indicated a three-factor structure. BSCQ-M scores showed convergent validity with past 30-day cannabis use. The BSCQ-M can be implemented quickly and effectively among justice involved youth. Abstract: Cannabis refusal self-efficacy, defined as confidence in the ability to refuse cannabis or to avoid cannabis use, is associated with decreased cannabis use. Juvenile justice-involved youth are at high risk for cannabis use and may have lower refusal self-efficacy. While court-involved, non-incarcerated (CINI) and incarcerated youth are groups that are both at high-risk for cannabis use, the experience of incarceration may impact the measurement of refusal self-efficacy for cannabis. The factor structure, measurement invariance, and concurrent validity of the Brief Situational Confidence Questionnaire for Cannabis (BSCQ-M) was assessed among CINI ( n  = 148) and incarcerated ( n  = 199) youth (80.7% male, Mage  = 16.3). Confirmatory factor analyses indicated that a correlated 3-factor model including positive/good times, negative internal, and negative external situational factors best fit the data. Multigroup measurement invariance testing revealed that the BSCQ-M demonstrated configural, metric, scalar, and residual invariance across CINI and incarcerated samples, indicating measurement invariance across the two groups. Negative binomial regressions revealed that BSCQ-M scores were significantly negatively associated with concurrent cannabis use. Results suggest that the BSCQ-M is a brief, psychometrically sound measure of refusal self-efficacy for cannabis among juvenile justice-involved youth that can be utilized with both CINI and incarcerated youth.